2022
DOI: 10.3389/fpsyg.2021.756570
|View full text |Cite
|
Sign up to set email alerts
|

Role of Responsible Leadership for Organizational Citizenship Behavior for the Environment in Light of Psychological Ownership and Employee Environmental Commitment: A Moderated Mediation Model

Abstract: The world is looking toward organizations for social responsibility to contribute to a sustainable environment. Employees’ organizational citizenship behavior for the environment (OCBE) is a voluntary environmental-oriented behavior that is important for organizations’ environmental performance. Based on social learning theory, this study examined the effects of responsible leadership in connection with OCBE by using a sample of 520 employees in the manufacturing and service sectors in China including engine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 69 publications
3
18
0
Order By: Relevance
“…In support of previous literature [ 9 , 62 ], the results show that residents’ environmental identification is directly and positively related to their environmental citizenship behavior in the private and public domains (H4, H5). Consistent with prior research on employees’ environmental citizenship behavior [ 20 , 64 ], the findings of this study indicate that environmental commitment triggers residents’ environmental citizenship behavior in the private and public domains (H6, H7). These findings underline the importance of environmental identification and environment commitment in driving residents’ private and public environmental citizenship behavior in rural destinations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In support of previous literature [ 9 , 62 ], the results show that residents’ environmental identification is directly and positively related to their environmental citizenship behavior in the private and public domains (H4, H5). Consistent with prior research on employees’ environmental citizenship behavior [ 20 , 64 ], the findings of this study indicate that environmental commitment triggers residents’ environmental citizenship behavior in the private and public domains (H6, H7). These findings underline the importance of environmental identification and environment commitment in driving residents’ private and public environmental citizenship behavior in rural destinations.…”
Section: Discussionsupporting
confidence: 90%
“…Commitment is a psychological state that can determine how people behave [ 63 ]. Studies on organizational behavior indicate that as the level of employees’ environmental commitment rises, there are more possibilities for them to adopt favorable behavior to improve the environment [ 20 , 63 , 64 ]. Empirical findings have also confirmed that environmental commitment can be translated into citizenship behavior for the environment.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This study aims to expand the existing literature as follows: First, in contrast with previous research (e.g., Jaiswal and Dhar, 2015 ; Shanker et al, 2017 ; Liu F. et al, 2019 ; Leyer et al, 2021 ), this study attempts to unfold the mechanisms through which organizational innovation climate affects employee innovative behavior, with leader–member paired questionnaires from a highly innovative sample in information transmission, information technology service, and financial industry to attenuate the common method bias. Second, drawing on the psychological ownership theory ( Pierce et al, 2001 , 2003 ; Van Dyne and Pierce, 2004 ), this study provides a new theoretical insights into the organizational climate–innovative behavior linkage by highlighting the positive role of psychological ownership in long-term organizational development from the perspective of employee innovative behavior, which is different from most of the literature on its role in employee organizational citizenship behavior (e.g., Jiang et al, 2019 ; Abbas et al, 2022 ). Third, by taking task interdependence as a moderating variable, this study responds to Hunter et al’s (2007) call for paying more attention to the moderators in the organizational climate–innovative achievements relationship at the job level.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, existing research has provided a series of evidence for this proposition. For example, many scholars found that responsible leadership could facilitate employees’ pro-environmental behavior ( Han et al, 2019a , b ; Afsar et al, 2020 ; Abbas et al, 2021 ; Tuan, 2022 ) and voluntary workplace green behavior ( Zhang et al, 2021 ). Accordingly, we propose:…”
Section: Theory and Hypothesesmentioning
confidence: 99%